EFEKTIVITAS PEMBIAYAAN MODAL USAHA TERHADAP PERKEMBANGAN UMKM: STUDI KASUS BMT BINA UMMAT SEJAHTERA KCU PONDOK GEDE - Sulthan Suci Yudhistira (2023)
Currently Micro, Small and Medium Enterprises (MSMEs) are important players in the progress of society. In the process of recovering the Indonesian economy, Micro, Small and Medium Enterprises (MSMEs) play a very important role. With a very large number of industries in every economic sector, making SMEs play an important role in the Indonesian economy. The purpose of this study was to analyze and determine the effectiveness of business capital financing for the development of MSMEs in BMT Bina Ummat Sejahtera KCU Pondok Gede. The research method used is descriptive qualitative using a case study approach. While data collection techniques using interviews, observation, and documentation. The selected informants consisted of 6 people consisting of operational managers and customers. The results of this study indicate that the business capital financing distribution scheme for BMT Bina Ummat Sejahtera KCU Pondok Gede uses a mudharabah contract scheme. Meanwhile, the measurement of the effectiveness of business capital financing distribution is measured using 5 indicators; target accuracy, goal attainment, program outreach, program monitoring and financing procedures confirmed to be running effectively and having a positive impact on the development and empowerment of MSMEs members of the BMT Bina Ummat Sejahtera KCU Pondok Gede. The limitation in this research is the difficulty of accessing the financial reports belonging to BMT Bina Ummat Sejahtera KCU Pondok Gede. The recommendation of this research is to be able to publish its financial reports on the official website of BMT Bina Ummat Sejahtera.